2013
DOI: 10.1371/journal.pone.0063892
|View full text |Cite|
|
Sign up to set email alerts
|

Human Papillomavirus Type 6 and 11 Genetic Variants Found in 71 Oral and Anogenital Epithelial Samples from Australia

Abstract: Genetic variation of 49 human papillomavirus (HPV) 6 and 22 HPV11 isolates from recurrent respiratory papillomatosis (RRP) (n = 17), genital warts (n = 43), anal cancer (n = 6) and cervical neoplasia cells (n = 5), was determined by sequencing the long control region (LCR) and the E6 and E7 genes. Comparative analysis of genetic variability was examined to determine whether different disease states resulting from HPV6 or HPV11 infection cluster into distinct variant groups. Sequence variation analysis of HPV6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 62 publications
6
26
1
Order By: Relevance
“…Regarding the low-risk groups, HPV-6 and 11 are the most prevalent26. In our study, HPV-6 was found in 20% of the samples.…”
Section: Discussionsupporting
confidence: 49%
“…Regarding the low-risk groups, HPV-6 and 11 are the most prevalent26. In our study, HPV-6 was found in 20% of the samples.…”
Section: Discussionsupporting
confidence: 49%
“…Some of the samples in which only HPV 6 or 11 were detected have been further investigated using laser capture micro dissection and have been confirmed to only contain these “low‐risk” types . Furthermore, a recent detailed evaluation of the HPV genotypes in these samples failed to detect any unusual genomic variants . Clearly the role of HPV 6 and 11 in the etiology of anal cancer warrants further investigations …”
Section: Discussionmentioning
confidence: 99%
“…uman papillomavirus 11 (HPV11), which belongs to species 10 of the Alphapapillomavirus genus (Alpha-PV), is etiologically associated with approximately 20% of anogenital warts and 30 to 40% of laryngeal papillomas (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). HPV11 is generally considered a low-risk HPV type due to its rare presence in HPVrelated cancers in humans, especially cervical cancer (9).…”
mentioning
confidence: 99%
“…On the basis of the analysis of 32 complete HPV11 genomes originating mainly from Slovenia, HPV11 genomic variants were classified into two sublineages: sublineage A1 (previously termed the "prototypic variant") and sublineage A2 (previously termed the "nonprototypic variant"). Three additional HPV11 genomic diversity studies that focused on samples from the head and neck and the anogenital regions and that described the variability of the HPV11 genome from ethnogeographically closed cohorts and/or focused on individual complete or partial HPV11 genomic regions have recently been published (7,27,28). Several HPV11 genomic variants with highly similar nucleotide profiles were identified in these studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation